A utilização dos processos biotecnológicos como diferencial produtivo das empresas nas incubadoras de negócios em Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The use of biotechnological processes stands out as a productive differentiator for companies in business incubators in Manaus-AM. The study analyzes the activities that drive the development of these processes in incubated companies that explore Amazonian biodiversity. The objectives focus on identifying these processes, R&D activities, workforce training and environmental guidelines. Methodologically, this research was a cross-sectional, exploratory descriptive study, of a qualitative and quantitative nature. Combining bibliographical research and semi-structured questionnaires. Seven incubators in the city of Manaus were selected, containing 55 biotechnological companies, between the months of June and October 2023. A total of 27 companies responded to the questionnaires, the majority working with various biotechnological processes. It is inferred that the incubated companies studied exhibit a diversity of biotechnological processes, ranging from the production of enzymes, DNA analysis, transformation of fresh products, development of enzyme blends, molecular certification of fish, production of biodegradable packaging, to the development of products such as soaps and exfoliants. This variety reflects the rich Amazonian biodiversity and the innovative capacity of companies in the region. Regarding the analysis of the educational level of employees at incubated companies, there was a significant focus on the advanced training of these individuals, with a large proportion of masters and doctors. This suggests a substantial investment in training and developing specialized skills crucial to the advancement of biotechnology. Finally, through this research it was concluded that biotechnology is emerging in startups in Amazonas, indicating that it is a growing practice for startups in the Amazon region, reconciling with sustainability based on the circular economy and that incubators play a vital role in supporting startups. that develop biotechnological processes. However, the need for a deeper analysis of the correlations between process complexity and choice of raw material was observed.
Keywords: Incubadoras de empresas - Manaus (AM); Biotecnologia - Inovações tecnológicas; CIENCIAS BIOLOGICAS; Incubadoras de empresas; Biotecnologia; Processos biotecnológicos; Inovação